Ecospaces of the Middle to Upper Paleolithic transition: The archaeofaunal record of the Iberian Peninsula. Issue 177 (April 2023) - Jones, Emily Lena; Carvalho, Milena
Abstract: The rich archaeofaunal record of Iberia provides a means of exploring potential differences between Neanderthal and anatomically modern human interactions with the environment. In this article, we present an analysis of Iberian archaeofaunas dating between 60 and 30 ka to explore if, how, and why the faunal ecospaces of Neanderthals and anatomically modern humans differed. We test for impacts of chronology (as a proxy for Neanderthal and anatomically modern human exploitation) and environmental regionalization (using bioclimatic regions) on archaeofaunal composition, using a combination of cluster (unweighted pair-group method using arithmetic averages) and nonmetric multidimensional scaling. Our chronological analysis finds no significant compositional difference between Neanderthal and anatomically modern mammalian faunal assemblages; however, bioclimatic regionalization is stronger in anatomically modern human–affiliated assemblages than in Neanderthal ones, a finding that may indicate a difference in site occupation duration or foraging mobility between Neanderthals and anatomically modern humans.